PENERAPAN COOPERATIVE LEARNING TEKNIK MAKE A MATCH MENGGUNAKAN AUTHENTIC ASSESSMENT SUB POKOK BAHASAN KUBUS DAN BALOK UNTUK MENINGKATKAN KETUNTASAN BELAJAR SISWA KELAS VIII-F SMP NEGERI 1 GUMUKMAS TAHUN AJARAN 2011/2012 - Vika, V; Suharto, S; Kristiani, Arika Indah (Department of Mathematics Education , University of Jember, 2012)
Abstract. This study aims to: improve the independence of students in learning mathematics through Cooperative Learning methods and make a match strategy using authentic assessment. This type of research is the Classroom Action Research (CAR) collaborative. The subjects are students in grade VIII SMPN I Gumukmas School Year 2011/2012, amounting to 33 students as subjects who received the action. Implementation of the action is the subject of research. Subjects who supported the implementation of the math are teachers and principals. Data collection methods are used the method of observation, test methods, reviews and documentation methods. Data analysis technique is implemented in a descriptive qualitative. It is found on the average the students activity improve 66,7% at siklus I become 78,8% at siklus II, and the teacher activity improve 4,66%. The classical thoroughness improve 33,34%. So the conclusion of this research is the application of the make a match approach can improve theostudent achievmentoinklearningomathematics. Key Words : Cooperative learning, Make a match Approach, Authentic Assessment